Fiscal Sustainability in Emerging Market Countries with an Application to Ecuador - Carlos Díaz Alvarado; Alejandro Izquierdo; Ugo Panizza (Inter-American Development Bank, Research Department, 2004)
This paper surveys the recent literature on fiscal sustainability, with particular emphasis on emerging market countries. It discusses the main elements that differentiate emerging market countries from industrial countries and then discusses how probabilistic models can help to evaluate fiscal sustainability in an uncertain environment. Based on this discussion, the paper uses Ecuador to illustrate an application of the probabilistic model, and of the framework to evaluate the impact of shocks to current account financing on sustainability.
Keywords: E62; O23; 330; Fiscal Sustainability; Debt; Default; Sudden Stop; Emerging Markets; Ecuador; Finanzpolitik; Haushaltskonsolidierung; Kapitalmobilität; Öffentliche Schulden; Theorie; Ecuador